Utilidade da radiografia panorâmica digital na detecção de calcificações na artéria de doentes renais crônicos. - Brasileiro Junior, Vilson Lacerda (2011)
The carotid artery calcification (CAC) is one of the most serious and frequent complications occurring in patients with chronic kidney disease. In recent years, the dental literature has warned dentists about the possibility of panoramic radiography to detect these lesions. However, little is known about the reliability of this method in the diagnosis of calcifications. The objective of this study was to evaluate by means of two scientific articles the prevalence of CAC in digital panoramic radiographs (DPR) of patients with chronic kidney failure under hemodialysis treatment and see if this examination can be reliable in the diagnosis of these lesions. The first article analyzed the prevalence of calcifications in the DPR of patients with chronic kidney failure and compared these results with the radiographic findings of a group of healthy patients. Statistical analysis using chi-square test revealed a significant difference (p <0.001) in the prevalence of these lesions among the study groups, since 28% (n = 14) of the radiographs of patients on hemodialysis had pictures of CAC, whereas only 2% (n = 1) radiographs of the control group had these images. The second article verified the reliability of the DPR in the diagnosis of CAC, comparing the results of that examination with ultrasonography (USG). The parameters used for this evaluation were precision, sensitivity, specificity and positive predictive value. The results showed that the panoramic radiograph was 71.43% accurate in diagnosing cases of CAC confirmed by ultrasound, with low sensitivity (37.93%), high specificity (95.12%) and good positive predictive value (84.61%). In addition, the McNemar test revealed a statistically significant difference (p <0.001) between the ability of DPR to diagnose CAC compared to the USG. On the above, we can conclude that patients with chronic kidney failure under hemodialysis treatment are significantly more affected by the CAC that the healthy population and that despite the DPR is not indicated as test of choice to investigate the presence of CAC, it can be a useful tool in the diagnosis of lesions in asymptomatic patients.